Physico-Chemical Changes in the KCl-MgCl2/La-FAU Composite Catalyst Induced by Oxidative Dehydrogenation of Ethane - Sajad, Mehran; Bulánek, Roman; Šlang, Stanislav (MDPI, 2021)
In this research, a binary eutectic composition of KCl and MgCl2 supported over lanthanum exchanged FAU (faujasite) zeolite has been investigated for the oxidative dehydrogenation (ODH) of ethane. The catalyst was prepared by the thermal treatment of La-FAU with a mechanical mixture of alkali chlorides under a flow of helium at 500 degrees C. The eutectic mixture of alkali chlorides formed at this temperature and a molten layer were spread over the support. Synthesized fresh and spent catalysts were characterized to obtain information about changes in crystallinity, textural properties, phase content, chemical composition, and morphology of the catalyst over the reaction time. The initial conversion of ethane was 80% with ethene as the main product (65% yield). The catalyst deactivation has been demonstrated over time on the stream (TOS). The characterization methods confirmed that the chlorine was being removed from the catalyst. The side products detected by mass spectroscopy, including chlorinated hydrocarbons, have been found as a key pathway of chlorine removal from the catalyst. The exchange of chlorine for oxygen in the catalyst led to a significant decrease in the activity and production of higher hydrocarbons and their oxygenates as side products of the ODH reaction.
Fyzikálně chemické změny v KCl-MgCl2/La-FAU katalyzátorech pro oxidativní dehydrogenaci etanu
Keywords: oxidative dehydrogenation; alkali chlorides; ethane; ethylene; oxidativní dehydrogenace; chloridy; etan; eten